Desarrollo de una aplicación móvil para seguimiento y control de ganado bovino de la hacienda San Gabriel, provincia Bolívar, Guaranda, año 2021 - Agualongo Caiza, Jessica Marisol (2022)
The main objective of the development of this research work was to develop a mobile application for the monitoring and control of cattle of the San Gabriel farm, in order to solve the problems of storage and management of information, for the development of the application we chose an agile methodology specifically Scrum, to learn more about the problems and processes of the farm, we chose to apply an interview and observation sheet. Once the information was collected, it was discovered that there is no similar research in the country. Regarding the problem, it was found that workers have difficulties in searching, saving and updating information requested by the owner and generated during daily activities. For the development of the mobile application a distributed architecture was implemented, using the following technologies for the presentation the React Native Framework was used, in conjunction with Expo, the Laravel Framework was used for the business logic layer, for data management Postgres, Mongo DB and SQLite were implemented. The GAPP application has modules for cattle management, production control, worker management, veterinary management, task management, reports, cattle sales management and a module for visitors. At the end of the research, once the results were analyzed and interpreted, we proceeded to calculate and test the hypothesis using the Chi-square method, which proved the hypothesis.